When does the support phase end in running? - Romanov, N. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The question of where the support phase ends in running is very important both for the science and practice of sports. Different distances and different speeds in running require different support time, efforts, cadence and stride length. What role does one body weight (BW) play in support in running? How is it related with the above parameters and what defines the end of support? Purpose: In this theoretical study it was attempted to find a hypothetical and practical answer to when the support phase ends in running. Methods: The ground reaction force (GRF) data and graphs from science literature (1, 2) and from own research data (3) were analyzed. The main data for the analysis was that of one body weight (BW) on the graph of the vertical component (Vc) and the peak of the horizontal component (PHc) of ground reaction force, and their time line during support. Results: It was found that PHc of GRF never occurred later than Vc of magnitude of 1 BW. Poor runners had PHc much earlier than Vc of GRF reached 1BW. Good runners had a tendency to have PHc of GRF closer to the time of 1BW. The same tendency was observed at different running speeds, from slower to faster. GRF data of animals is similar to that of good runners. Discussion/Conclusion: This data raises the question about the reason behind the relations between 1 BW and PHc of GRF and how is it related with the end of support in running. Why do these data coincide? From our point of view, GRF graphs represent two different sides of support. On the one side, we observe its mechanical part from the first to the last moment of the contact with the ground. The other side, more meaningful for living organisms, the biological side, was left in the shadows and was almost imperceptible. This side is related with the necessity to change the support. The reason for this is that the body`s perception has more important and more valuable information than speed, stride length and frequency to consider and that is 1BW. Our analysis shows that perception of BW is the boundary for support phase, its measure and guidance as to how to interact with support common to all living organisms on Earth. It also defines the time of the appearance of HPc of GRF as well, because it is the action of disengagement with support.